SOME QUESTIONS OF DEVELOPMENT OF RECREATIONAL GEOGRAPHY (Scientific journal of the Fergana State University, 2025)
In article are analyzed a place of recreational geography in system of geographical sciences and recreational potential of Republic Uzbekistan. Also, socio-political, spiritual and pedagogical factors of the development of tourism in the new stage of development of Uzbekistan were studied, and the possibilities of its development were studied.